2009
DOI: 10.1182/blood-2009-06-230037
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel regulators of hematopoietic stem cell development through refinement of stem cell localization and expression profiling

Abstract: The first adult-repopulating hematopoietic stem cells (HSCs) are detected starting at day 10.5 of gestation in the aorta-gonads-mesonephros (AGM) region of the mouse embryo. Despite the importance of the AGM in initiating HSC production, very little is currently known about the regulators that control HSC emergence in this region. We have therefore further defined the location of HSCs in the AGM and incorporated this information into a spatial and temporal comparative gene expression analysis of the AGM. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 51 publications
3
78
0
Order By: Relevance
“…Supporting the idea that these populations are also functionally dissimilar is our finding that AGM HSCs respond differently from E14.5 FL and adult BM HSCs to the deletion of the cyclin-dependent kinase inhibitor, p57Kip2 (Cdkn1c). Loss of p57Kip2 in both E14.5 FL and adult BM HSCs leads to reduced self-renewal and maintenance, respectively [22,23], whereas we have observed an expansion of HSCs in p57Kip2 null AGMs [24]. More recently, it has been shown that despite expression of both retinoic acid receptors (RARs) a and c on HSCs, the functionally predominant RAR transitions throughout development.…”
Section: Definitive Hscs Have Distinct Properties In the Adult And Thmentioning
confidence: 56%
See 1 more Smart Citation
“…Supporting the idea that these populations are also functionally dissimilar is our finding that AGM HSCs respond differently from E14.5 FL and adult BM HSCs to the deletion of the cyclin-dependent kinase inhibitor, p57Kip2 (Cdkn1c). Loss of p57Kip2 in both E14.5 FL and adult BM HSCs leads to reduced self-renewal and maintenance, respectively [22,23], whereas we have observed an expansion of HSCs in p57Kip2 null AGMs [24]. More recently, it has been shown that despite expression of both retinoic acid receptors (RARs) a and c on HSCs, the functionally predominant RAR transitions throughout development.…”
Section: Definitive Hscs Have Distinct Properties In the Adult And Thmentioning
confidence: 56%
“…The niche is the convergence of metabolic, humoral, paracrine, neural, structural, and physical signals that act to regulate stem cells [42]. For HSCs, it is HSCs emerge/mature from pre-HSCs [3] No de novo generation, but rapid expansion of HSCs [18] Largely quiescent unless activated [90,91] Response to p57kip2 knockout Increased repopulation ability [24] Reduced repopulation in tertiary recipients [22] Conditional knockout results in reduced repopulation capacity [23] …”
Section: Environmental Regulation Of Hscsmentioning
confidence: 99%
“…In E11.5 AGMs, Lgr5, and Ki67 double positive cells were observed mainly within the intra-aortic clusters ( Fig. 2A), where HSCs emerged and matured (13,14). In E12.5 embryos, the main HSC expansion sites switched to the fetal liver, where proliferative Lgr5-GFP cells increased from 52% at E11.5 to 65.8% at E12.5 (Fig.…”
Section: Detection Of Lgr5-expressing Cells In Agm and Fetal Liver Bementioning
confidence: 95%
“…In mouse embryos, the generation of HSCs initiates in AGM on E10.5, and continues very rapidly through E12 (12)(13)(14)(15). A pool of HSCs is formed predominantly in fetal liver on E12 by recruiting definitive HSCs via the blood circulation from extra-hepatic sources (AGM region and/or placenta) (15,16).…”
mentioning
confidence: 99%
“…1,2 The later appearance of definitive HSPCs in the aorta-gonad-mesonephros region raises the question whether cells identified in this region (i) arrive from the yolk sac at the time when the heart begins to beat and initiates blood flow, 3 (ii) are specified in the aortic wall from a local pool of stem cells as a response to blood-flow shearing forces 4 or (iii) are derived from a subpopulation of primitive mesodermal/germ line cells that migrate through the embryo proper on their way to colonize the genital ridges. 5 Later, at the second trimester of gestation, HSPCs accumulate in the fetal liver (FL), which becomes a major hematopoietic organ in the developing embryo. 6 Finally, at the beginning of the third trimester of gestation, HSPCs leave the FL and begin to colonize in the developing bone marrow (BM).…”
Section: Introductionmentioning
confidence: 99%